2021
DOI: 10.1016/j.ssaho.2021.100139
|View full text |Cite
|
Sign up to set email alerts
|

Social distanciation through COVID-19: A narrative analysis of Indian Peri-Urban Elderly

Abstract: The world encountered an emergent issue of great concern, regarding the new pandemic virus termed as ‘Novel Coronavirus (COVID-19)’. This pandemic situation has disconcerted the socio-economic and psychological situations of people and their livelihoods, thus, disturbing societal equilibrium. Social distancing is considered to be an influential weapon to restrict this virus transmission. Like many others, especifically, the elderly people, face pressing difficulties in their daily life-world. Thus, a qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…This study shows that knowledge of COVID-19 has a positive and significant effect on social distancing between people. These survey findings are consistent with previous research (Besser et al, 2020 ; Das and Bhattacharyya, 2021 ; Jogezai et al, 2021 ; Kniffin et al, 2021 ). These studies show that, when people understand the severity of the pandemic and its life-threatening consequences, their defense mechanisms keep them away from others to avoid unknowingly contracting the virus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study shows that knowledge of COVID-19 has a positive and significant effect on social distancing between people. These survey findings are consistent with previous research (Besser et al, 2020 ; Das and Bhattacharyya, 2021 ; Jogezai et al, 2021 ; Kniffin et al, 2021 ). These studies show that, when people understand the severity of the pandemic and its life-threatening consequences, their defense mechanisms keep them away from others to avoid unknowingly contracting the virus.…”
Section: Discussionsupporting
confidence: 92%
“…Social media use increased during the pandemic (Zhao and Zhou, 2021 ) owing to social distancing and quarantining of the individuals to prevent the spread of infection caused by COVID-19. Previous studies have been carried out on COVID-19 from different perspectives like digital learning during the emergence of COVID-19 virus (Hasan and Bao, 2020 ; Aditya, 2021 ; Chaturvedi et al, 2021 ; Deshpande and Mhatre, 2021 ; Smith et al, 2021 ), its impact on the economies of different countries (Hasan and Bao, 2020 ; Ye et al, 2020 ; Ali et al, 2021 ; Bhattacharya and Banerjee, 2021 ; Cuschieri and Grech, 2021 ; Delbiso et al, 2021 ; Donnarumma and Pezzulo, 2021 ; Klasche, 2021 ; Mahi et al, 2021 ; Prempeh, 2021 ; Roy et al, 2021 ), its role in the global health crisis (Abdalla et al, 2021 ; Ankrah et al, 2021 ; Chaturvedi et al, 2021 ; Chirisa et al, 2021 ; Donnarumma and Pezzulo, 2021 ; Hannam-Swain and Bailey, 2021 ; Klasche, 2021 ; Prempeh, 2021 ; Sarfraz et al, 2021 ; Wang et al, 2021 ; Zhao and Zhou, 2021 ) and the worst of all its impact on the mental wellbeing of people (Ciotti et al, 2020 ; Elmer et al, 2020 ; Filipova et al, 2020 ; Lee, 2020 ; Serafini et al, 2020 ; Adom et al, 2021 ; Chaturvedi et al, 2021 ; Coupet et al, 2021 ; Das and Bhattacharyya, 2021 ; Deshpande and Mhatre, 2021 ; Hannam-Swain and Bailey, 2021 ; Kareem, 2021 ; Li and Cao, 2021 ; Pandya and Lodha, 2021 ; Saha et al, 2021 ; Tonkin and Whitaker, 2021 ; Xiong et al, 2021 ). However, understanding the role of online social media use to meet the social needs after the closure of physical social interactive places amid COVID-19 is critical (Haman, 2020 ; Jogezai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The economic ramifications of physical distancing due to COVID-19 are well known, but the cultural implications are largely unexplored [4]. Therefore, it is necessary to have an insight into the perspective of Indian elderly on QoL.…”
Section: Impact Of Covid-19 On Qol Of Elderly: An Indian Scenariomentioning
confidence: 99%
“…Das et al carried a study about narrative analysis and found that social isolation and distancing is a major strategy to reduce chance of spreading infection and we also found same results in narrated evaluation at early stage of disease whereas Muslim Scholars advised in the light of Hadith that affected persons should not be removed from affected area of outbreak so that spread of disease be prevented. [15] Aazam et al carried a study on fear and economic crisis in an analysis of Pakistani Newspaper's from cartoons of COVID-19 and found results from visual images e.g., a middle aged man on one hand airing to coronavirus and increasing its size while simultaneously on the other hand he looks anxious and worried about its massive spread but ignoring that he is the cause of spread of disease due to non-opting of precautionary measures against COVID-19.We agrees with Azam about giving message through visual picture as one of mode of communication where we have seen in semiotic analysis of our study about different factors which communicated to public through an easily understandable photograph. [16] Davies stated that in world with fast-paced, globalized travel and trade, an early detection of communicable disease outbreaks has become ever more important to prevent rapid spread of disease.…”
Section: Analysis About Global Bifurcation Of Casesmentioning
confidence: 99%